Volume of breast tissue excised during breast-conserving surgery in patients undergoing preoperative systemic therapy - Valejo,Fernando Antonio Mourão (2013)
PURPOSE: We aimed to determine whether clinical examination could adequately ascertain the volume of tissue to be resected during breast-conserving surgery after neoadjuvant therapy. METHODS: We reviewed the clinical reports of 279 patients with histologically diagnosed invasive breast carcinomas treated with neoadjuvant therapy followed by surgery or with primary surgery alone. We estimated volumes of excised tissues, the volume of the tumor mass and the optimal volume required for excision based on 1 cm of clear margins. The actual excess of resected volume was estimated by calculating the resection ratio measured as the volume of the resected specimen divided by the optimal specimen volume. The study endpoints were to analyze the extent of tissue resection and to ascertain the effect of excess resected tissue on surgical margins in both groups of patients. RESULTS: The median tumor diameter was 2.0 and 1.5 cm in the surgery and neoadjuvant therapy groups, respectively. The median volume of resected mammary tissue was 64.3 cm³ in the primary surgery group and 90.7 cm³ in the neoadjuvant therapy group. The median resection ratios in the primary surgery and neoadjuvant therapy groups were 2.0 and 3.3, respectively (p<0.0001). Surgical margin data were similar in both groups. Comparison of the volume of resected mammary tissues with the tumor diameters showed a positive correlation in the primary surgery group and no correlation in the neoadjuvant therapy group. CONCLUSION: Surgeons tend to excise large volumes of tissue during breast-conserving surgery after neoadjuvant therapy, thereby resulting in a loss of the correlation between tumor diameter and volume of the excised specimen.